Intelligent flowerpot - WANG WEIXIN; LI SIHAI (2017)
The invention discloses an intelligent flowerpot. The intelligent flowerpot comprises a flowerpot body (1), a water storage container (2), a water delivery pipe (7), a control switch (4) arranged on the water delivery pipe (7), a water level monitoring device (3) located on the inner wall of the bottom of the water storage container (2), a storage battery (5), a solar cell panel (6), a rotating device (8), a controllable water delivery pipe (9), a sprinkler head (10) and a humidity sensor (11) located in soil of the flowerpot body. According to the intelligent flowerpot, the water delivery pipes are not prone to be blocked, water can be automatically supplemented to flowers, an external power supply is not needed, and a planter can be reminded to add water; in addition, the height of the sprinkler head is regulated according to the actual conditions of the flowers, and uniform sprinkling is achieved. 本发明公开了种智能花盆，包括花盆本体（1）、储水容器（2）、输水管（7）、设置在所述输水管（7）上的控制开关（4）、位于所述储水容器（2）底部内壁上的水位监测装置（3）、储蓄电池（5）、太阳能电板（6）、旋转装置（8）、